Superfluid Spin-up: Three-dimensional Simulations of Post-glitch Dynamics in Neutron Star Cores - J. R. Fuentes; Vanessa Graber (The Astrophysical Journal)
Neutron stars show a steady decrease in their rotational frequency, occasionally interrupted by sudden spin-up events called glitches. The dynamics of a neutron star after a glitch involve the transfer of angular momentum from the crust (where the glitch is presumed to originate) to the liquid core, causing the core to spin up. The crust–core coupling, which determines how quickly this spin-up proceeds, can be achieved through various physical processes, including Ekman pumping, superfluid vortex-mediated mutual friction, and magnetic fields. Although the complex nature of these mechanisms has made it difficult to study their combined effects, analytical estimations for individual processes reveal that spin-up timescales vary according to the relative strength of Coriolis, viscous, and mutual friction forces, as well as the magnetic field. However, experimental and numerical validations of those analytical predictions are limited. In this paper, we focus on viscous effects and mutual friction. We conduct nonlinear hydrodynamical simulations of the spin-up problem in a two-component fluid by solving the incompressible Hall–Vinen–Bekarevich–Khalatnikov equations in the full sphere (i.e., including r = 0) for the first time. We find that the viscous (normal) component accelerates due to Ekman pumping, although the mutual friction coupling to the superfluid component alters the spin-up dynamics compared to the single-fluid scenario. Close to the sphere’s surface, the response of the superfluid is accurately described by the mutual friction timescale irrespective of its coupling strength with the normal component. However, as we move deeper into the sphere, the superfluid accelerates on different timescales due to the slow viscous spin-up of the internal normal fluid layers. We discuss potential implications for neutron stars, and requirements for future work to build more realistic models.